2015
DOI: 10.1080/00268976.2015.1087600
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, properties and application of Coulomb Sturmians defined in spheroidal coordinates

Abstract: Coulomb Sturmian amplitude functions are derived in prolate spheroidal coordinates and are presented in a closed algebraic form. Spheroidal Sturnian functions are revealed to be related to the polynomial solutions of Heun's confluent equation. A reduction of symmetry from spherical to axial leads to the coupling of spherical polar orbitals and the formation of hybrid orbitals. The contribution of each spherical orbital into a hybrid orbital depends strongly on distance R from a nucleus to the dummy centre, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[71], the interbasis transformation between the parabolic and spherical bases has been constructed. However, a similar transformation between the prolate spheroidal and spherical bases was not built in an analytical approach since it required a complex integration between confluent Heun [75], associated Laguerre, and generalized Jacobi polynomials [36]. These integrations have not been analytically calculated yet, to the best of our knowledge.…”
Section: Nine-dimensional Micz-kepler Problemsmentioning
confidence: 99%
“…[71], the interbasis transformation between the parabolic and spherical bases has been constructed. However, a similar transformation between the prolate spheroidal and spherical bases was not built in an analytical approach since it required a complex integration between confluent Heun [75], associated Laguerre, and generalized Jacobi polynomials [36]. These integrations have not been analytically calculated yet, to the best of our knowledge.…”
Section: Nine-dimensional Micz-kepler Problemsmentioning
confidence: 99%
“…[25] The solutions of the H 2 + molecule ion problem have been also analyzed in terms of hypergeometric functions, [26] the Heun confluent functions, [27,28] and Coulomb Sturmians. [29,30] Series solutions have also been given for the spectrum of H 2 + . [31] Upon thorough inspection of the literature surveyed here, it is found that all the tabulated spectra contain at most 15 significant digits, which is a product of the limitation of floating-point calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Both the lowerand higher-lying states of the H + 2 have been recently computed using semiclassical approximations [22][23][24], and variational approaches [25]. The solutions of the H + 2 molecule ion problem have been also analyzed in terms of hypergeometric functions [26], the Heun confluent functions [27,28], and Coulomb Sturmians [29,30]. Series solutions have also been given for the spectrum of H + 2 [31].…”
Section: Introductionmentioning
confidence: 99%